Presenting a Productivity Improvement Model Based on Artificial Intelligence Practices in Small and Medium Enterprises to Achieve Sustainable Development - Fotohi Ardakani, Hossein; Keramati, Mohamadali; Mehrinejad, Safiyeh; Mehrani, Azadeh (Management Strategies and Engineering Sciences, 2024)
In the current era, artificial intelligence (AI) is recognized as one of the vital tools on the path toward sustainable development, assisting businesses in optimizing resources, reducing costs, and increasing efficiency. This study, focusing on automating production processes, optimizing energy consumption, and improving human resource management, demonstrates that the use of AI can have positive effects on innovation and production flexibility. The aim of this research is to design and present a productivity improvement model based on AI practices in small and medium enterprises (SMEs) to achieve sustainable development. The study was organized using the Delphi method and thematic analysis, classified as applied in terms of objective and qualitative in terms of data collection methods. The statistical population includes experts and senior managers of SMEs, who were localized and selected based on the Delphi process. The data collection tool for this research was a Delphi questionnaire, and after collecting the information, the codes from the written interviews were analyzed using thematic analysis. The validity of the research was ensured by expert agreement, and its reliability was obtained through consensus of opinions and face validity. The qualitative research method, utilizing a thematic network with 118 basic themes, 24 organizing themes, and 7 overarching themes, revealed that all identified themes are relevant according to experts, and there is a high level of agreement on their importance.